Second Language Acquisition Research: A Proposal for a Shift of Emphasis in Applied Linguistics - Luis Fernando Gómez; Luz Mariela Osorio; Luz Janneth Osorio (Asociación Colombiana de Profesores de Ingles, 2016)
The central concern of this paper is to interpret a field as diverse and controversial as applied linguistics and language teaching while naturally acknowledging and respecting other interpretations of the same phenomena. The presenters divide the paper into three main parts: the first part consists of a short general overview of Applied Linguistics in language teaching. The second part presents an examination of current trends in those disciplines which underlie second language teaching, namely, linguistics, psychology and pedagogy. Finally, the third part considers Second Language Acquisition Research (SLAR) as a possible avenue of answers for the question of a shift of emphasis in the field and proposes a framework for explaining Second Language Acquisition.